The effect of waist hip ratio on the various stress types in I year Indian medical students - A. K., Sunitha Priya; Panchu, Pallavi; Babu, Rose; Bahuleyan, Biju (International Journal of Research in Medical Sciences, 2017)
Background: A medical student faces tremendous academic and non-academic stress owing to the vast curriculum and inadequate time. The impact of stress results in detrimental mental and physical health which is assessed here using stress questionnaires and anthropometric parameters. Stress need not be only academic. Hence it becomes vital to identify and target the specific and common non-academic stressors to enable the students to have a stress-free learning environment. The objective of this study was to find the inter relationship between waist hip ratio (WHR) and various stressors the student is exposed to. Methods: 97 I year medical students participated in this cross-sectional study and were administered the medical student stress questionnaire (MSSQ), a validated tool and the anthropometric measurements (waist and hip circumference, waist hip ratio, body mass index) were taken. The data was analyzed using SPSS version 22. Results: The study showed a negative correlation of WHR with all the stress parameters of which inter personal relationship stress (IRS) and teaching learning related stress (TLRS) were significant. Conclusions: Increasing the duration of I year MBBS course and helping learners acclimatize to the new study environment may help in reducing stress. Stress relaxation techniques, psychological counselling and strengthening the mentor- mentee programs along with exercise regimen may aid in the stress reduction process and facilitate physical health.